FORMATION AND DEVELOPMENT STAGES OF TRADE UNION ORGANIZATIONS IN INDEPENDENT UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
This article describes the processes of reforming the trade union system and the essence of effective solutions to the obstacles that are a source of it. The stages of formation and development of trade union organizations in independent Uzbekistan are revealed. Also, in the post-independence period, trade unions were formed as independent organizations from the state. These associations began to carry out their activities independently.